The intermediate Accounting series : Volume 2 - Robes, Nenita S.; Empleo, Patricia M. (Mandaluyong city, 2016)
?Intermediate Accounting Series Volume 2 by Patricia M. Empleo and Nenita S. Robles is a comprehensive textbook that delves into advanced financial accounting topics. It covers areas such as inventories, property, plant, and equipment, intangible assets, investment properties, and biological assets. The book emphasizes both initial and subsequent measurement of these assets, their financial statement presentation, and related accounting concerns. Designed for students and professionals, it aims to enhance understanding of complex accounting standards and their practical applications.
Keywords: Accounting